2020
DOI: 10.1590/1678-4324-2020200304
|View full text |Cite
|
Sign up to set email alerts
|

Role of ACE2 Gene Expression in Renin Angiotensin System and Its Importance in Covid-19: In Silico Approach

Abstract: We aimed to analyze the expression profile of ACE2 and similar genes with ACE2, predict the number of variations in ACE2, detect the suspected SNPs on ACE2 gene, and perform the pathway analysis of renin-angiotensin system (RAS) and protein absorption-digestion. Moreover, we have predicted the generelated diseases with ACE2. STRING was used to analyze functionally similar genes with ACE2. Exome Variant Server, SIFT, Polyphen2 were used to predict the number of variations in ACE2 and detect the suspected SNPs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Recently, studies have demonstrated that prostate cancer is linked with COVID-19 [33]. Especially, based on a study, prostate cancer patients who received androgen therapy had a lower risk for SARS-COV-2 infection compared to patients who did not (receive androgen deprivation therapy) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that prostate cancer is linked with COVID-19 [33]. Especially, based on a study, prostate cancer patients who received androgen therapy had a lower risk for SARS-COV-2 infection compared to patients who did not (receive androgen deprivation therapy) [20].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in TLR-encoding genes, namely TLR2, TLR4, TLR5, TLR9, and TLR10 have been associated with H. pylori infection risk and/or chronic gastritis (166, 169-173). On the other hand, carriers of the TLR1 rs4833095 T allele presented decreased risk of infection and chronic atrophic gastritis (173,174). Lower risk of the latter was also observed in individuals carrying the TLR10 rs10004195 T allele, suggesting a potential role of these SNPs in gastric pathogenesis associated with H. pylori (174,175).…”
Section: Microbial Activation Of Toll-like Receptorsmentioning
confidence: 92%
“…ACE2 is a well-defined integral membrane metalloproteinase involving in the renin-angiotensinaldosterone system (RAAS) and is highly abundant throughout the body ( Barker and Parkkila, 2020 ; Bourgonje et al, 2020 ; Tas et al, 2020 ; Tay et al, 2020 ). Both ACE2 and TMPRSS2 are especially present on targeted alveolar epithelial type 2 cells in the human body ( Wiersinga et al, 2020 ).…”
Section: Pathophysiology and Clinical Presentation Of Covid-19mentioning
confidence: 99%
“…Both ACE2 and TMPRSS2 are especially present on targeted alveolar epithelial type 2 cells in the human body ( Wiersinga et al, 2020 ). Although ACE2 expressing cells can mainly facilitate cell entry for the virus, the revealed pathophysiological mechanisms of COVID-19 represent that not all organs share the same infection state and outcome, which may be due to different parameters affecting the receptor expression, disease severity, and progress ( Bourgonje et al, 2020 ; Tas et al, 2020 ; Wiersinga et al, 2020 ).…”
Section: Pathophysiology and Clinical Presentation Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation